Apoptotic extracellular vesicles carrying Mif regulate macrophage recruitment and compensatory proliferation in neighboring epithelial stem cells during tissue maintenance. - Safia A Essien; Ivanshi Ahuja; George T Eisenhoffer (PLoS Biology)
Apoptotic cells can signal to neighboring cells to stimulate proliferation and compensate for cell loss to maintain tissue homeostasis. While apoptotic cell-derived extracellular vesicles (AEVs) can transmit instructional cues to mediate communication with neighboring cells, the molecular mechanisms that induce cell division are not well understood. Here, we show that macrophage migration inhibitory factor (Mif)-containing AEVs regulate compensatory proliferation via ERK signaling in epithelial stem cells of larval zebrafish. Time-lapse imaging showed efferocytosis of AEVs from dying epithelial stem cells by healthy neighboring stem cells. Proteomic and ultrastructure analysis of purified AEVs identified Mif localization on the AEV surface. Pharmacological inhibition or genetic mutation of Mif, or its cognate receptor CD74, decreased levels of phosphorylated ERK and compensatory proliferation in the neighboring epithelial stem cells. Disruption of Mif activity also caused decreased numbers of macrophages patrolling near AEVs, while depletion of the macrophage lineage resulted in a reduced proliferative response by the epithelial stem cells. We propose that AEVs carrying Mif directly stimulate epithelial stem cell repopulation and guide macrophages to cell non-autonomously induce localized proliferation to sustain overall cell numbers during tissue maintenance.